Unravelling the origin of the capacitance in nanostructured nitrogen-doped carbon - NiO hybrid electrodes deposited with laser. Issue 11 (1st June 2022) - Lebière, Pablo García; György, Enikö; Logofatu, Constantin; Naumenko, Denys; Amenitsch, Heinz; Rajak, Piu; Ciancio, Regina; Pérez del Pino, Ángel
Abstract: The full knowledge of the charge storage mechanisms occurring in complex composite electrodes is key for the straightforward development of advanced electrochemical capacitors. In this work, hybrid electrodes composed of reduced graphene oxide, multiwall carbon nanotubes and NiO nanostructures were fabricated through reactive inverse matrix assisted pulsed laser evaporation technique. Nitrogen doping of the carbon nanostructures was carried out by introducing ammonia, urea and melamine precursors in the target. The N-doped graphene electrodes exhibited a significant capacitance enhancement as compared to non-doped ones. This fact is commonly ascribed to faradaic mechanisms. However, our structural-compositional studies point to a significant change of the structural configuration of the composites at the nanoscale upon the nitrogen functionalization as the source of the electrodes' capacitance enhancement. The composites fabricated with urea precursor exhibited the highest capacitance, and this fact was associated with the presence of pyridinic N groups that triggered the formation of a high amount of structural defects (vacancies – boundaries) and microporosity, not observed in the samples synthesized with other precursors that mainly contained pyrrolic-graphitic N.